Pemakaian Herbal Serbuk Biji Pepaya Matang dalam Pengendalian Infeksi Ascaris suum pada Babi - Ardana, Ida Bagus Komang; Bakta, I Made; Damriyasa, I Made (Jurnal Veteriner; Vol 12 No 4 (2011), 2012)
A study on vermisidal effect of ripe papaya seed powder against egg and worm of A.suum in landracepig was done. Twenty four pigs age 8-12 weeks were used in this study using pre-test and post-test groupexperimental design. The pigs were randomly divided into four groups : a group of pigs with no treatmentas a control (P0) and other three groups were given 1 g/kg body weigh (P1), 3 g/kg bw (P2) during threeconsecutive days and treated with 12.5% zodalben oral 0.5 mg of albendazole (P3). The number of A.suumand its eggs per gram (EPG) were identified by using international harmonization and anthelminticefficacy guideline. Then follow by observation and calculation of EPG, fecal egg count reduction (FECR),and the efficacy of the powder for seven days. The result showed there was a significant lower number ofA.suum infestation in the treated group of pigs compared to the control group as it was shown by theincrease of the efficacy against worms and the FECR value. However, there were different effects on theefficacy and FECR between the group that treated with 1 g/kg bw of the ripe papaya seed powder (efficacy75% and FECR 92.4%) compared to the groups that treated with 3 g/kg bw of the seed powder, and treatedwith zodalben 12.5% (both efficacy and FECR were 100%). It can be concluded that herbal powder of ripepapaya seed has a potential effect to be vermisidal, especially for A.suum.
Keywords: herbal ripe papaya seed powder, worm, Ascaris suum